If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3r + 4(-3r + 4) = 91 Reorder the terms: -3r + 4(4 + -3r) = 91 -3r + (4 * 4 + -3r * 4) = 91 -3r + (16 + -12r) = 91 Reorder the terms: 16 + -3r + -12r = 91 Combine like terms: -3r + -12r = -15r 16 + -15r = 91 Solving 16 + -15r = 91 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -15r = 91 + -16 Combine like terms: 16 + -16 = 0 0 + -15r = 91 + -16 -15r = 91 + -16 Combine like terms: 91 + -16 = 75 -15r = 75 Divide each side by '-15'. r = -5 Simplifying r = -5
| 3(y-2)=6(y-1)-34 | | -15=-11 | | -4(1+4x)+3x=-69 | | 14x+21=14 | | 0.9x-1=0.8 | | -3(-4r+4)=-60 | | 4y+-32-5=51 | | 6x+4+8y-7=107 | | 5(5a-3)=-90 | | b-1+5(2v+1)=-3(v+4) | | 6x+4+8y-7+73=180 | | 5x+12=115 | | 8y-7+73+6x+4=180 | | 2(cos^2)x+5sin(x)=4 | | y-5=-3y+5 | | 3(y-9)-7=-4(-5y+8)-3y | | 5m+2-3m=46 | | 8u+1.7=3 | | -4(5k+3)=-112 | | 3n+16+5n+20=90 | | 81-y=8y-18 | | 7x-63=(-28) | | 6(y+3)=-2(4y-2)+8y | | 4/7×3 | | -3(5k+1)-k=61 | | b^2+20b-96=0 | | .6(x)+.33=1 | | (nm^-4/(2m^-2)^-3(2nm^2))^4 | | u+1=10 | | -4(5k+1)-k=61 | | 6(2f-12)+15-13f=-3 | | 6(3-x)-5x=-4 |